Principles in Sasak Local Wisdom as Character Education Values for Children - Ahmad Yasar Ramdan; Abdullah Muzakar (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2022)
Sasak people’s life is strongly embedded by the philosophical values in each tradition that can lead them to have better perspectives. This study aimed to describe the values of character education in the local wisdom of the Sasak tribe, and the process of instilling character education values in the Sasak family. An ethnographic qualitative approach was used to obtain the information based on the research objectives. The data were collected through observations, interviews, documentations, and FGD techniques.The data were obtained from the families, traditional leaders, and communities. The results of the study revealed that the character values as the identity of the Sasak people were found in four principles, namely: wirame principle, wirage principle, wirase principle, and wibusane principle. The process of transmitting character values to children was done by giving knowledge, doing habituation, and imitation of the parents’ good habits and behaviors. The value of local wisdom in the traditions could be used as an insight for parents and society as educational references to build children’s characters